Recovery sleep attenuates impairments in working memory following total sleep deprivation - Peng, Ziyi; Hou, Yanhong; Xu, Lin; Wang, Haiteng; Wu, Shuqing; Song, Tao; Shao, Yongcong; Yang, Yan (Frontiers in Neuroscience, 2023)
The detrimental effects of sleep deprivation (SD) on cognitive function and quality of life are well known, and sleep disturbances are a major physical and mental health issue worldwide. Working memory plays an important role in many complex cognitive processes. Therefore, it is necessary to identify strategies that can effectively counteract the negative effects of SD on working memory. In the present study, we utilized event-related potentials (ERPs) to investigate the restorative effects of 8 h of recovery sleep (RS) on working memory impairments induced by total sleep deprivation for 36 h. We analyzed ERP data from 42 healthy male participants who were randomly assigned to two groups. The nocturnal sleep (NS) group completed a 2-back working memory task before and after normal sleep for 8 h. The sleep deprivation (SD) group completed a 2-back working memory task before and after 36 h of total sleep deprivation (TSD) and after 8 h of RS. Electroencephalographic data were recorded during each task. The N2 and P3 components—which are related to working memory—exhibited low-amplitude and slow-wave characteristics after 36 h of TSD. Additionally, we observed a significant decrease in N2 latency after 8 h of RS. RS also induced significant increases in the amplitude of the P3 component and in the behavioral indicators. Overall, 8 h of RS attenuated the decrease in working memory performance caused by 36 h of TSD. However, the effects of RS appear to be limited.